Hydrogen Solid State Storage on MgH[sub.2] Compacts for Mass Applications - Fruchart, Daniel; Jehan, Michel; Skryabina, Nataliya; de Rango, Patricia (Metals (Basel ), 2023)
The mass storage of hydrogen is a challenge considering large industrial applications and continuous distribution, e.g., for domestic use as a future energy carrier that respects the environment. For a long time, molecular hydrogen was stored and distributed, either as a gas (pressurized up to 75 MPa) or as a cryogenic liquid (20.4 K). Furthermore, the atomic storage of hydrogen in the solid-state form via metallic or covalent compounds is still the subject of intense research and limited to a small scale for some practical developments. In addition, other type H chemical storage routes are being tested, such as ammonia and LOHC (Liquid Organic Hydrogen Carrier), etc. In any case, the main constraint remains security. However, Hydrogen Solid State Storage (HSSS) using MgH[sub.2] bodies has been shown to be feasible in terms of process and safety. Furthermore, its intrinsic volumetric densification was proven to be much better performing with 106:70:45 kgH[sub.2]/m[sup.3] for solid (RT):LH (20.4 K):gas (75 MPa), respectively. Very early on, fairly reactive MgH[sub.2]-based pellets were produced (for max. ~27 tons/year) at McPhy Energy using a series of unique and self-built installations. Thus, the design of large instrumented reservoirs was undertaken thanks to fundamental research first carried out at the CNRS. So, prototypes of storage units from 100 to ~5500 kWh have been produced. However, McPhy took other routes a few years ago (smelting and refueling stations) because the HSSS market was not merging at that time. Today, a new operator, Jomi–Leman, therefore, decided to try the challenge again focusing on applications with on-site production and mass HSSS.